2020
DOI: 10.1253/circj.cj-19-0926
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Volumetric and Functional Assessment of the Right Ventricle in Hypoplastic Left Heart Syndrome After Fontan Palliation, Utilizing 3-Dimensional Speckle-Tracking Echocardiography

Abstract: Background: Right ventricular (RV) volumetric and functional assessments are both crucial for the management of patients with hypoplastic left heart syndrome (HLHS). 3-dimensional echocardiography (3DE) for volume measurements and 2D speckle-tracking echocardiography (2D-STE) for strain analysis are performed separately. 3D-STE is capable of evaluating those parameters simultaneously and providing principal strain (PS), unifying the concepts of myofiber orientation and contraction into a single, maximal contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…Therefore, 3D echocardiography could provide an alternative method to CMR for the serial assessment of the size and function of the single ventricle. In a study of paediatric Fontan patients, it has been shown similar to this study that 2D and 3D volumes correlate strongly with each other, in addition to 3D-derived speckle tracking analysis suggesting 3D derived ejection fraction reflects cardiac mechanics as well [18]. CMR is only available in specialised centres and some patients are unable to undergo CMR due to claustrophobia or are contraindicated.…”
Section: Discussionsupporting
confidence: 78%
“…Therefore, 3D echocardiography could provide an alternative method to CMR for the serial assessment of the size and function of the single ventricle. In a study of paediatric Fontan patients, it has been shown similar to this study that 2D and 3D volumes correlate strongly with each other, in addition to 3D-derived speckle tracking analysis suggesting 3D derived ejection fraction reflects cardiac mechanics as well [18]. CMR is only available in specialised centres and some patients are unable to undergo CMR due to claustrophobia or are contraindicated.…”
Section: Discussionsupporting
confidence: 78%
“…We acknowledge that our strain analysis with radially reconstructed long-axis cine CMR was based on the original in-house algorithm. Although measurements of RV PS with echocardiography using commercial software have been reported 17 , 18 , no software has been established for RV PS for CMR. We considered that the values of PS, GCS, and GLS were clinically reasonable and reliable in the study populations.…”
Section: Discussionmentioning
confidence: 99%
“…Three-dimensional STE analysis for the right ventricle is shown in Figure 2 . Its accuracy and reproducibility in assessing RV function have been confirmed in patients with transplanted hearts, pulmonary hypertension, and hypoplastic left heart syndrome after Fontan palliation [ 63 , 67 , 68 , 69 ]. Moreover, we previously investigated the feasibility and accuracy of 3D-STE for the quantification of RVLS in comparison with CMR imaging in a large number of study populations with a wide variety of RVEF and cardiovascular pathologies, and found that the 3D-RVFWLS values correlated better than 2D-RVFWLS values with CMR values (0.85 vs. 0.64) with smaller bias and narrower limits of agreement.…”
Section: Rv Longitudinal Strain Analysismentioning
confidence: 99%